Wealth distribution and retirement preparation among early savers - Lindsay Jacobs; Elizabeth Llanes; Kevin Moore; Jeffrey P. Thompson; Alice Henriques Volz (Federal Reserve Bank of Boston, 2020)
This paper develops a new combined-wealth measure by augmenting data on net worth from the Survey of Consumer Finances with estimates of defined benefit (DB) pension and expected Social Security wealth. We use this concept to explore retirement preparation among two groups of households in pre-retirement years (aged 40 through 49 and 50 through 59), and to explore the concentration of wealth. We find evidence of moderate, but rising, shortfalls in retirement preparation. We also show that including DB pension and Social Security wealth results in markedly lower measures of wealth concentration, and it slightly moderates trends toward a higher concentration over time.
Keywords: D31; D63; H55; I32; 330; retirement adequacy; wealth inequality; Social Security